Fragmentation study of major spirosolane‐type glycoalkaloids by collision‐induced dissociation linear ion trap and infrared multiphoton dissociation Fourier transform ion cyclotron resonance mass spectrometry. (29th September 2016) - Lelario, F.; Labella, C.; Napolitano, G.; Scrano, L.; Bufo, S. A.
Abstract : Rationale: Glycoalkaloids play a key role in the plant protection system against phytopathogens including fungi, viruses, bacteria, insects and worms. They can be toxic to humans if consumed in high concentrations causing gastrointestinal disturbances. Methods: The structural characterization of the major spirosolane glycoalkaloids, solasonine, solamargine, α‐tomatine and dehydrotomatine, were investigated by positive electrospray ionization (ESI) coupled with a hybrid linear ion trap (LIT) and Fourier transform ion cyclotron resonance (FTICR) mass spectrometer. Tandem mass spectrometric analysis of spirosolane glycoalkaloids was performed by both collision‐induced dissociation (CID) within the LIT and infrared multiphoton dissociation (IRMPD) in conjunction with the FTICR cell. Results: Several common product ions were observed, generated by losses of the sugar moiety or aglycone fragmentation in the B‐ or E‐ring, that can provide information on the accurate mass of aglycone and the primary sequence and branching of the oligosaccharide chains. Thanks to the multistage CID it was possible to understand the fragmentation pathways and thanks to the high resolution of IRMPD‐FTICR the elemental compositions of product ions were obtained. Conclusions: Because the investigated tandem mass spectra data were acquired with high mass accuracy, unambiguous interpretation and determination of the chemical compositions for the majority of detected fragment ions were feasible. From these data, generalized fragmentation pathways were proposed, providing guidance for the characterization of unknown glycoalkaloids in plants. Copyright © John Wiley & Sons, Ltd.